Evaluation the Effectiveness of Green Zinc Oxide Nanoparticles on the Anti-Inflammatory Effect of Dexamethasone and Its Side Effects in Rats - Elham, A. Mobarez (South Valley University, 2018)
Green synthesis of nanoparticles is considered an ecofriendly technology because it does not involve toxic chemicals. In this study, green zinc oxide nanoparticles (7-25 nm) were synthesized from olive plant and examined for its anti-inflammatory activities alone or with dexamethasone in rats. Seventy rats were randomly allocated into 7 groups (10 rats/group). Group 1 served as a negative control. Other rats in the six groups were injected with formalin into the intra planter paws of right hind limb (50ul) followed by administration of investigated agents as following; group 2 used as control positive for inflammation. Group 3 and 4 were administrated dexamethasone at 2 doses; 2 and 5mg/ kg b.wt. (i.m), respectively. Group 5 was treated with zinc oxide nanoparticles at dose of 25mg/ kg b.wt.(i.p). Groups 6 and 7 were treated with Zinc oxide nanoparticles at dose of 25 mg/kg b. wt. (i.p) and dexamethasone at doses of 2 and 5mg/kg b. wt. (i.m), respectively. All treatments were continuous for 5 successive days. Representative blood and tissue samples for immunological, chemical and pathological investigations were collected. The present study refers to the anti -inflammatory effect of both zinc oxide nanoparticles and dexamethasone through variable pathways; mixed treatment between green Zinc oxide nanoparticles and dexamethsone improve the dysregulated biochemical effects induced by inflammation. ZnO nano-particles affect mainly Th2 which enhanced by dexamethasone that had mainly immune- suppressive effect on B-lymphocytes. Despite the recorded anti-inflammatory effect, attention to side effects such as genotoxicity recorded in that study, should be considered. We could conclude that although green zinc oxide nanoparticles may be considered as a potential treatment for inflammatory conditions, but it enhances the apoptotic effect of dexamethasone with end-result of (transient) genotoxic effect.